MENGURANGI KEBISINGAN DARI BUNYI KLAKSON SEBAGAI BENTUK CARA MENGHARGAI DALAM LINGKUP MASYARAKAT BALIKPAPAN - Diana Pabulang; Putry Regina Ayu Prayoga (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Traffic noise is an urban environmental problem that negatively impacts physical and psychological health, particularly due to the use of vehicle horns. However, in Balikpapan, a unique phenomenon was found in the form of minimal horn use, creating a calmer traffic environment. This study used descriptive qualitative methods through literature studies, observations, and regulatory reviews to analyze horns as a driving culture, the impact of minimal noise on health, the synergy of regulations with public awareness, and Balikpapan's opportunities as a model for traffic ethics education. The results show that the habit of not honking has become a new social norm that increases comfort and reduces stress in the community. This success is supported by government regulations and collective public awareness. Balikpapan also has the potential to become an example of traffic ethics education at the national level. In conclusion, the minimal use of horns in Balikpapan is not only a good traffic practice but also a strategy to build a more polite, healthy, and sustainable driving culture.